The contribution of the TSNIGRI Diamond laboratory to the scientific treasury of Yakutia - Alexander V. Тolstov; Nikolay N. Zinchuk (Руды и металлы, 2022)
Brief information is given on the main stages of scientific activity or the half-century history of the Research Geological Enterprise (NIGP) of PJSC ALROSA, confirming their inheritance from the initial stages of the enterprise (Diamond Laboratory, YaOKI, YaF and YANIGP TsNIGRI) in various scientific areas (geology, tectonics, stratigraphy, paleotectonics, paleogeography, petrophysics, petrography, petrology, petrochemistry, geophysics, geochemistry, complex study of primary and secondary minerals, etc.). Attention is focused on individual stages of such studies, caused by the expansion of the geography of research and the development of a modern set of methods for studying the material composition of rocks. Over the half-century period of activity of the Diamond Laboratory – NIGP PJSC ALROSA (PJSC) in Yakutia, the company’s scientists have transferred and implemented hundreds of forecast and methodological recommendations into geological exploration, published thousands of articles, published more than a hundred monographs on a wide range of areas of geology of solid minerals and, first of all, for diamonds.